Flow-metabolism coupling in human visual, motor, and supplementary motor areas assessed by magnetic resonance imaging. - Chiarelli, P; Bulte, D; Gallichan, D; Piechnik, S; Wise, R; Jezzard, P (2007)
Combined blood oxygenation level-dependent (BOLD) and arterial spin labeling (ASL) functional MRI (fMRI) was performed for simultaneous investigation of neurovascular coupling in the primary visual cortex (PVC), primary motor cortex (PMC), and supplementary motor area (SMA). The hypercapnia-calibrated method was employed to estimate the fractional change in cerebral metabolic rate of oxygen consumption (CMR(O2)) using both a group-average and a per-subject calibration. The group-averaged calibration showed significantly different CMR(O2)-CBF coupling ratios in the three regions (PVC: 0.34 +/- 0.03; PMC: 0.24 +/- 0.03; and SMA: 0.40 +/- 0.02). Part of this difference emerges from the calculated values of the hypercapnic calibration constant M in each region (M(PVC) = 6.6 +/- 3.4, M(PMC) = 4.3 +/- 3.5, and M(SMA) = 7.2 +/- 4.1), while a relatively minor part comes from the spread and shape of the sensorimotor BOLD-CBF responses. The averages of the per-subject calibrated CMR(O2)-CBF slopes were 0.40 +/- 0.04 (PVC), 0.31 +/- 0.03 (PMC), and 0.44 +/- 0.03 (SMA). These results are 10-30% higher than group-calibrated values, and are potentially more useful for quantifying individual differences in focal functional responses. The group-average calibrated motor coupling value is increased to 0.28 +/- 0.03 when stimulus-correlated increases in end-tidal CO(2) are included. Our results support the existence of regional differences in neurovascular coupling, and argue for the importance of achieving optimal accuracy in hypercapnia calibrations to resolve method-dependent variations in published results.